Uji Triaksial Unconsolidated-Undrained pada Campuran Tanah Lanau - Kapur - Abu Sekam Padi dan Serat Karung Plastik - Widianti, Anita; Hartono, Edi; Muntohar, Agus Setyo (Semesta Teknika, 2008)
Geotechnical and mechanical behaviour of soil stabilized with lime-rice husk ash and strengthened by randomly placed plastic fiber depends on the portions of the added materials and curing time. This research investigates the effect of the waste plastic sack fibers portion and the curing time to the stress â€“ strain relationship and to the shear strength parameters of the mixture. In this study the portions of lime and rice husk ash were set as constant to the value of 12% and 24% respectively. The effect of four waste plastic sack fibers portion variation from 0.1% to 0.8% was measured by unconsolidated-undrained triaxial test. The samples were tested at 7, 14 and 21 days after mixing. In general, according to the test result, the inclusion of randomly waste plastic sack fiber and curing time have enhanced the shear strength parameters, the peak stress and the strain before failure.Â  With 0.2% fiber content, the cohesion and the internal friction angle values of the samples have increased 335% and 409% respectively compared with those of the samples having no added materials.